1996
DOI: 10.1159/000177081
|View full text |Cite
|
Sign up to set email alerts
|

Floating Right Heart Thrombi and Pulmonary Embolism: Diagnosis, Outcome and Therapeutic Management

Abstract: The aim of this study was to analyze clinical and echographic findings and to assess therapeutic management in 14 floating right atrial thrombi diagnosed with systematic echocardiography in 200 consecutive patients with proven pulmonary embolism. Auscultatory findings were abnormal in 7 cases, 4 of them showing signs of tricuspid obstruction. Echocardiography displayed a mobile ovoid, polycyclic or worm-like right atrial mass, always associated with signs of cor pulmonale. Four patients (29%) died, 2 of them b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0
8

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 13 publications
0
84
0
8
Order By: Relevance
“…Central venous catheterrelated PE occur more often with thrombi adherent to catheters (sleeve thrombi) compared to venous wall (mural thrombi). 30,31 In summary, PE occurs in up to one-third of patients with UEDVT and in 15 to 20% of those with CVC-related UEDVT.…”
Section: Risk For Pulmonary Embolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Central venous catheterrelated PE occur more often with thrombi adherent to catheters (sleeve thrombi) compared to venous wall (mural thrombi). 30,31 In summary, PE occurs in up to one-third of patients with UEDVT and in 15 to 20% of those with CVC-related UEDVT.…”
Section: Risk For Pulmonary Embolismmentioning
confidence: 99%
“…In two cohort studies involving 200 and 130 patients with confirmed PE, RHTE were detected, primarily by transthoracic echocardiography (TTE), in 7 and 18% of subjects, respectively. 31,32 A postmortem study documented concurrent RHTE and PE in 6% of cases. 33 More recently, the International Cooperative Pulmonary Embolism Registry 34 reported RHTE in 4% of 1,113 patients with PE undergoing echocardiography.…”
Section: Risk For Pulmonary Embolismmentioning
confidence: 99%
“…4 But, there is no consensus related to management of the right atrial thrombi, which is less than 2 cm in diameter. It is recommended emergent surgery in these patients when thrombi greater than 2 cm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the prevalence of RHT in PE cases between 7% and 18% (1,2). Detection of RHT is very important because of documented high mortality rate (>40%) (3,4).…”
Section: Introductionmentioning
confidence: 99%